[Afisz. Incipit] V Akademickie Mistrzostwa Polski : Gdańsk 28.VI.-3.VII.1955. (Gdańsk : [wydawca nieznany], 1955)
Afisz informujący o zawodach w Gdańsku.
Keywords: Studenci -- Polska -- 1945-1970 -- druki ulotne; Sport -- Polska -- 1945-1970 -- druki ulotne; Gdańsk (Polska) -- 1945-1970 -- druki ulotne; Druki ulotne -- 1945-1970.